‘Arrogant and seductive’: disclaiming the opinion of G. L. Koster with regard to the authors of traditional Malay literature - Hamdan, Rahimah; Sujud, Arbaie (Asian Online Journals, 2015)
This paper re-evaluates the opinion of G.L. Koster with regard to the authors of traditional Malay literature, specifically of Panji Literature. The spread of Islam in the Malay world awakened writers to the purpose, facts and methods of literary creativity with regard to matters concerning ‘penmanship’. The responsibilities of Malay writers became more complex with the emergence of the Javanese influence, which brought a breath of fresh air into the world of Malay literature. Writers of the Panji Literature genre very daringly included elements of sexuality in their works, something that was considered a taboo subject that was not to be openly discussed in Malay society. Furthermore, the authors of Panji Literature failed to apply ‘the idea of the book’ in their compositions. Consequently, G.L. Koster labelled the authors of Panji Literature as ‘dalang’.The question is, if the authors were ‘dalangs’, then why did they also incorporate elements of trust, advice and guidance in the genre to balance the entertainment function? Being a Western scholar, did G.L. Koster understand the conventions of Malay authorship? By carrying out a textual analysis of three selected texts, namely Hikayat Panji Semirang, Hikayat Chekel Waneng Pati and Syair Ken Tambuhan, this study will challenge the role of the authors of the Panji Literature, who have been classified as ‘dalangs’ by G.L. Koster. The study found that the authors of the Panji Literature were intellectuals of their time who abided by the conventions of Malay writing. Therefore, based on their wisdom, they managed to adapt the elements of sexuality that enabled the Panji Literature to be accepted by the Malay-Muslim community. This was highly consistent with the conventions of Malay writing that focus on benefitting the audience and not simply composing blindly.